Por caminos migrantes hacia la conciencia de una identidad abierta (Altre Modernità, 2009)
The stifling Argentinean dictatorship has elicited a series of reflections on Argentineans's cultural roots and, at the same time, it has called into question the notion of Argentinean exceptionalism. All this has brought to re-think and to re-evaluate the migratory past of Argentina, especially in light of the economic policy of the country that lead to the 2001 default. The political and economic events have had their reflections on the literary production, in particular on memoirs and pseudo-memoirs. The object of my essay is the work of AntonioDal Masetto, mostly known for his novels about migration. In particular, I will focus on his most recent writing in which the condition of the migrant is no longer a personal and familial concern but it becomes a contemporary and universal paradigm. For the purpose of my essay, I will use the by-now classic theories of Edouard Glissant, Jacques Derrida and Loretta Baldassar about migration.